The Public Interest in the Digital Age: Exploring the Emerging Roles and Governance Models of the AI as a Common Good - Wei, Siying; Ge, Zhenxuan; Tan, Consilz (Journal of Ecohumanism, 2024)
With the continuous development of artificial intelligence, we are living through the era of digital transformation, and the fourth Industrial Revolution is a paradigm change with unprecedented speed, scale, scope and complexity, and is fundamentally transforming production, consumption and society as a whole. As the basic unit of public management research, data has established a strong connection between the promotion of digital revolution and the change of public management research paradigm. The rise of AI technologies has enhanced AI governance and brought unprecedented help to policymakers. This study has used a cross-sectional quantitative design to capture perception and attitude towards AI as common good from a sample of 400 Chinese responders coming from diverse age, group and occupation categories. The key factors which measured were public awareness of AIGC, the extent of its utilization in government policy, public attitudes toward AIGC, and public participation in policy development. The findings indicated that public understanding and trust are paramount to successfully integrate Ai as common good in governance framework. Public enthusiasm and participations are highly affected by trust and public understanding. To deliver policies without much resistance, heightened awareness, participations and trust becomes essential.